SOCIAL NETWORKS AND ONLINE JOURNALISM. CLASSIFICATION AND AUDIENCE OF SOCIAL NETWORKS - Berdiyorova Sevinch Aliddin qizi (Western European Studies, 2024)
This article describesocial networks information and reflections on social media and online journalism
Keywords: social network; Facebook